Source of drinking water and other risk factors for dental fluorosis in Sri Lanka - Van Der Hoek, W.; Ekanayake, L.; Rajasooriyar, L.D.; Karunaratne, R. (Taylor & Francis Ltd, 2003)
This study was done to describe the association between source of drinking water and other potential risk factors with dental fluorosis. Prevalence of dental fluorosis among 518 14-year-old students in the south of Sri Lanka was 43.2%. The drinking water sources of the students were described and fluoride samples were taken. There was a strong association between water fluoride level and prevalence of fluorosis. Tea drinking before 7 years of age was also an independent risk factor in a multivariate analysis. Having been fed with formula bottle milk as an infant seemed to increase the risk although the effect was not statistically significant. No clear effects could be found for using fluoridated toothpaste, occupation of the father, and socio-economic status. Drinking water obtained from surface water sources had lower fluoride levels (median 0.22 mg l71) than water from deep tube wells (median 0.80 mg l71). Most families used shallow dug wells and these had a median fluoride value of 0.48 mg l71 but with a wide range from 0.09 to 5.90 mg l71. Shallow wells located close to irrigation canals or other surface water had lower fluoride values than wells located further away. Fluoride levels have to be taken into account when planning drinking water projects. From the point of view of prevention of dental fluorosis, drinking water from surface sources or from shallow wells located close to surface water would be preferable.
Keywords: Fluoride; Dental fluorosis; Drinking water; Risk factors; Sri Lanka